2011
DOI: 10.3109/10715762.2011.581279
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin: A new antioxidant that exerts its cytoprotective effect independent on Heme Oxygenase-1

Abstract: Neutrophil Gelatinase-Associated Lipocalin (NGAL/Lcn2), a member of the lipocalin family, has a variety of functions. There are extensive studies examining the expression of NGAL under harmful conditions. However, its precise function remains poorly understood. Heme Oxygenase 1 (HO-1) is an enzyme with well-established cytoprotective effects. Previous work showed that NGAL induces expression of HO-1. Interestingly, the same stimuli induced the expression of both NGAL and HO-1. The current study was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 26 publications
3
41
1
3
Order By: Relevance
“…The acutephase glycoprotein LCN2 is active under inflammation, apoptosis, and suppression of bacterial growth. There is recent evidence that Lcn2 also has a pivotal role in the protection against oxidative stress during hypoxia/reoxygenation in vitro (30) and that it acts as an antioxidant (31). Still, we could not detect …”
Section: Hyperoxia-induced Transcriptional Changescontrasting
confidence: 54%
“…The acutephase glycoprotein LCN2 is active under inflammation, apoptosis, and suppression of bacterial growth. There is recent evidence that Lcn2 also has a pivotal role in the protection against oxidative stress during hypoxia/reoxygenation in vitro (30) and that it acts as an antioxidant (31). Still, we could not detect …”
Section: Hyperoxia-induced Transcriptional Changescontrasting
confidence: 54%
“…It has also been reported that NGAL may play a role in renal adaptation to diabetes, probably as a defensive mechanism to mitigate tubular injury (Bolignano et al, 2009b). NGAL has also been reported to have antioxidant properties (Roudkenar et al, 2007(Roudkenar et al, , 2008(Roudkenar et al, , 2011Bahmani et al, 2010). Of interest, in our study, renal NGAL increased in diabetic rats, and suramin intervention further increased renal NGAL.…”
Section: Downloaded Fromsupporting
confidence: 57%
“…Importantly, these markers were higher in patients with reduced RBF and predicted the changes in single-kidney GFR after 3 months of stenting. In a similar pattern, NGAL can be protective against acute ischemic injury, although it is most often utilized as a biomarker for AKI [36]. Our results using BOLD MRI suggest that residual accumulation of deoxyhemoglobin after contrast imaging can persist for at least 24-27 h and extend results observed in experimental rat models that demonstrate renal hypoxia measured by BOLD MRI after injection of iodinated contrast [37].…”
Section: O R I G I N a L A R T I C L Esupporting
confidence: 72%